Masters of Their Own Destiny: Minorities' Right to Effective Participation in Public Life in Vietnam - Friberg,Erik (2002)
The main international provisions concerning minorities' right to participation in public life at national and local levels are enshrined in Article 2 of the UN Minority Declaration in conjunction with Article 25 of the ICCPR, providing minorities the right to take part in the conduct of public affairs. Vital adjacent political rights, include the freedom of association as enshrined in Article 2(4) of the UN Minority Declaration, which in conjunction with Article 22 of the ICCPR provides the right to establish and maintain minority associations. As most UN Member States, Vietnam has accepted international obligations to ensure de jure and de facto compliance with the international standards concerning minorities' right to effective participation in public life, guaranteeing its citizens of all ethnicities equal enjoyment and non-discrimination. However, international human rights law grants a wide latitude for States to comply with the right to effective participation in public life in general and in devising their electoral systems in particular. Vietnam's constitution and laws promote the equality between its 54 different ethnic groups, where the 53 ethnic minority groups constitute approximately 14% of the population. The ethnic minorities enjoy higher representation in the National Assembly than their share of the population, although the ethnic minority deputies appear to have a weaker voice relative to deputies from the ethnic majority group. The Ethnic Council, a parliamentary organ, has far-reaching powers in the legislative and executive processes. Elections to the National Assembly are held according to the principles of universal, equal, direct and secret suffrage. Voting material, however, appear to be limited or non-existing in minority languages. While exercising the democratic centralism principle, Vietnam is in a process of decentralisation promoting direct participation in decision-making at the local levels. Decree 29 (1998), provides a legal framework which, despite several obstacles in the implementation, should enable ethnic minorities to participate in local public decisions that affect them and the regions they inhabit. Although civil society in Vietnam yet is very weak in an international comparison, during the 1990s a legal framework has been put in place enabling some NGOs in Vietnam to emerge, while being monitored quite closely. While a mushrooming of de facto associations at local level is taking place, these are mainly established and enabled to perform socio-economic gap-filling functions, while policy-oriented associations are scarce. The developments have however opened the door for informal influence for ethnic minorities in decision-making at local and national level. While the Vietnamese Government is taking many steps to promote the participation of ethnic minorities, various socio-economic reasons hinder an enhanced participation of Vietnam's ethnic minorities in public life. Ensuring international standards of participation in public life and freedom of association interrelate with socio-economic development and re-enforce eachother. The study concludes with some practical recommendations of furthering minorities' participation in public life in Vietnam, including support of a Law on Minorities and Law on Association reflecting international standards and clarifying regulations on the democratic rights at the grassroots level.
Keywords: Komparativ rätt